Ozone and Air Quality Over Lake Michigan - Oster, Joseph (My University, 2015)
The purpose of this study is to find out what the air quality is like over the lake and to determine how air pollutants travel in the transition environment between the coast and the lake.
Color poster with text, maps, and graphs.
Keywords: Community Multi-scale Air Quality Model (CMAQ); Lake Michigan; Air quality; Ozone; Posters